2009
DOI: 10.1093/ejechocard/jen199
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of patients with undocumented arrhythmias occurring in adults late after repair of tetralogy of Fallot

Abstract: Our present data suggest that undocumented arrhythmias are most likely SVTs and are associated with increased RA size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Most of these predictors correlated to the risk of atrial fibrillation rather than AFL/IART, which is more likely to be pertinent in a TOF population. QRSd, as demonstrated in various TOF cohorts, is a univariate predictor of atrial arrhythmias; whereas P‐R prolongation has also been shown to be a univariate predictor of atrial arrhythmias in TOF patients late after repair …”
Section: Discussionmentioning
confidence: 98%
“…Most of these predictors correlated to the risk of atrial fibrillation rather than AFL/IART, which is more likely to be pertinent in a TOF population. QRSd, as demonstrated in various TOF cohorts, is a univariate predictor of atrial arrhythmias; whereas P‐R prolongation has also been shown to be a univariate predictor of atrial arrhythmias in TOF patients late after repair …”
Section: Discussionmentioning
confidence: 98%
“…Bonello et al 10 have previously described the morphological and haemodynamic characteristics of tetralogy of Fallot patients with atrial arrhythmias; of 154 patients, atrial tachyarrhythmias – sustained atrial tachyarrhythmias or atrial fibrillation – were observed in 11, a slightly lower incidence than has previously been reported, and were predicted by right atrial area on cardiac magnetic resonance imaging. Another study 11 examined the echocardiographic profiles of tetralogy of Fallot patients with palpitations but no documented tachycardia and also noted that the only significant difference in echocardiographic parameters between those with and without a history of palpitations was right atrial size. Our study in contrast highlights that atrial tachyarrhythmias are not only associated with right atrial enlargement but also with an increase in left atrial size.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography-based study found that most of undocumented arrhythmias were likely to be supraventricular and linked to increased right atrial (RA) size [27].…”
Section: Supraventricular Arrhythmiasmentioning
confidence: 99%